Two unusual cases of PLA2G6-associated neurodegeneration from India - Shilpa D Kulkarni; Meenal Garg; Rafat Sayed; Varsha A Patil (Annals of Indian Academy of Neurology, 2016)
Phospholipase A2-associated neurodegeneration (PLAN) comprises of three disorders with overlapping presentations. The most common of these is classical or infantile-onset phospholipase A2-associated neurodegeneration, also known as infantile neuroaxonal dystrophy (INAD). Only 1 case of INAD has been reported from India till now. We report two genetically confirmed patients seen at a tertiary care pediatric hospital. Both these patients presented with infantile onset of neuroregression. We believe that INAD is underrecognized and underreported from India.